2010
DOI: 10.1093/nar/gkq1029
|View full text |Cite
|
Sign up to set email alerts
|

The mRNA cap-binding complex stimulates the formation of pre-initiation complex at the promoter via its interaction with Mot1p in vivo

Abstract: The cap-binding complex (CBC) binds to the cap structure of mRNA to protect it from exonucleases as well as to regulate downstream post-transcriptional events, translational initiation and nonsense-mediated mRNA decay. However, its role in regulation of the upstream transcriptional events such as initiation or elongation remains unknown. Here, using a formaldehyde-based in vivo cross-linking and chromatin immunoprecipitation assay in conjunction with transcriptional, mutational and co-immunoprecipitational ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 116 publications
3
38
0
Order By: Relevance
“…The coimmunoprecipitation (co-IP) assay was performed as done previously (26,27) and is briefly described in the supplemental material.…”
Section: Wce Preparation and Western Blot Analysismentioning
confidence: 99%
“…The coimmunoprecipitation (co-IP) assay was performed as done previously (26,27) and is briefly described in the supplemental material.…”
Section: Wce Preparation and Western Blot Analysismentioning
confidence: 99%
“…In this direction, we first analyzed the role of CBC in association with RNA polymerase II with ADH1. We have recently demonstrated that both Cbp20p and Cbp80p are recruited to ADH1 (Lahudkar et al 2011). The deletion of CBP80 impairs the recruitment of Cbp20p (Lahudkar et al 2011), but does not alter Cbp20p's stability (Lahudkar et al 2011).…”
Section: Resultsmentioning
confidence: 98%
“…We have recently demonstrated that both Cbp20p and Cbp80p are recruited to ADH1 (Lahudkar et al 2011). The deletion of CBP80 impairs the recruitment of Cbp20p (Lahudkar et al 2011), but does not alter Cbp20p's stability (Lahudkar et al 2011). Therefore, we have used the Dcbp80 mutant for analysis of the effect of CBC on the association of RNA polymerase II with ADH1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations